2001
DOI: 10.1186/1471-2458-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Brief report on the effect of providing single versus assorted brand name condoms to hospital patients: a descriptive study

Abstract: ObjectivesThis study examined condom acquisition by persons in a hospital setting when single versus assorted brand name condoms were provided.MethodsCondom receptacles were placed in exam rooms of two clinics. During Phase 1, a single brand name was provided; for Phase 2, assorted brand names were added. Number of condoms taken was recorded for each phase.ResultsFor one clinic there was nearly a two-fold increase in number of condoms taken (Phase 1 to Phase 2); for the second clinic there was negligible diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, there is some support for focus group participants' suggestion that condom distribution would be especially effective if the condoms were free and if a variety of brands and types were made available (J. Williams, Christensen, Cagle, & Homan, 2001). Given the relative cost of providing condoms versus health care for HIV-positive persons (Pinkerton, Johnson-Masotti, Holtgrave, & Farnham, 2001), the extent to which a large-scale condom availability program would be effective among current and former drugusing women needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is some support for focus group participants' suggestion that condom distribution would be especially effective if the condoms were free and if a variety of brands and types were made available (J. Williams, Christensen, Cagle, & Homan, 2001). Given the relative cost of providing condoms versus health care for HIV-positive persons (Pinkerton, Johnson-Masotti, Holtgrave, & Farnham, 2001), the extent to which a large-scale condom availability program would be effective among current and former drugusing women needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of one study that found that condom acquisition increased by increasing interest in condoms through having multiple condom brands available. 44 Currently, some CBOs attempt to increase interest (and thus use) in condoms through providing various colors; understanding the importance of brand and color preferences of users and potential users deserves consideration in condom promotion.…”
Section: Condom Acquisition and Preferences 865mentioning
confidence: 99%